The teaching of ethics in Canadian Schools of Management and Administrative Studies - Singh, Jang B. (Journal of business ethics, 1989)
Business ethics has been described as a prime academic growth industry. This paper reports the findings of a survey aimed at establishing the status of ethics in the curricula of Canadian Schools of Management and Administrative Studies. It was found that twenty-three of the forty-two responding schools offer courses in business ethics and that they offer a total of twenty-five ethics courses, twenty of which are offered as electives. Forty-two percent of the schools not offering a course in business ethics plan to offer such a course by 1989. This means that by 1989 seventy-four percent of the responding schools should have a business ethics component in their curricula.